Upaya Bimbingan Belajar Terhadap Anak Taman Pendidikan Qur’an Dalam Mengatasi Rendahnya Sumberdaya Manusia Di Wilayah Desa Bungkuk Kecamatan Parang Kabupaten Magetan - Andhita Risko Faristiana; M.Khoirul Minan; Elsya Laras Sinta (Universitas 45 Surabaya, 2023)
For everyone education is where people will be very competitive in life in the world. In addition, a good education will create a good mental condition in a person, so that it will have an impact on increasing creativity. This tutoring is one of the efforts to improve Human Resources, especially for children by utilizing the learning facilities at the Al-Qur'an Education Park. This study aims to overcome the low learning styles of children in Bungkuk Village, Parang, Magetan. The method used in this community service research is the Asset Based Community Development (ABCD) method which prioritizes the utilization of assets or potential. The results of this community service research prove that this tutoring activity is an effort to improve human resources in terms of reading, writing, arithmetic and worship practices. This can be seen from the enthusiasm of the children in participating in existing guidance activities, gaining new knowledge, and being more enthusiastic about reciting the Koran..